WOMEN ENTREPRENEURSHIP IN THE TERTIARY SECTOR WITH SPECIAL REFERENCE TO TIRUNELVELI DISTRICT OF TAMIL NADU (International Journal of Food and Nutritional Sciences, 2022)
Entrepreneurship refers to the function made by entrepreneurs. It is an exclusive concept. Entrepreneurs are based on purposeful and systematic innovation. Women entrepreneurship means women engaging themselves in a purposeful activity to earn or main profit in the process of production and distribution of goods and services. Women entrepreneurs are the women or group of women who initiate, organise and operate a business enterprise. The Government of India has defined Women Entrepreneurs as “an Enterprise owned and controlled by a women having a minimum financial interest of 5 per cent of capital and giving at least 51 per cent of the employment generated in enterprise to women”. The entrepreneurial activities before 1857 were mainly confined to the British Businessmen and trading firms, participation of Indian people was negligible. The period after 1857 witnessed slow growth of Indian entrepreneurship. From the very beginning women have been the best managers of the kitchen and have solely dominated the area of household activities. The general attitude of women entrepreneurs is that they are the makers of papads, masalas, pickles and household goods. But nowadays the non-traditional enterprises are easily managed by women entrepreneurs. They made steady progress well as leading consultants, publishers, exporters of machinery, manufacture of electric goods, exporters of garments, designer’s interior decorators and the like.